Tuesday

September 16, 2014

September 16, 2014

Posted by **alejandro** on Monday, March 14, 2011 at 4:50pm.

example- y=x-2 y=4x+1

- pre algebra -
**Reiny**, Monday, March 14, 2011 at 5:25pmset y = y

4x + 1 = x - 2

you finish it.

- pre algebra -
**Jessica**, Monday, March 14, 2011 at 5:26pmMultiple the first equation by -1:

-y=-x+2

Add it from the second one to get:

y=4x+1 +(-y=x+2)= 0=3x+3

Subtract 3 from both sides:

-3=3x

Divide by 3

x=-1

Plug it in for one equation:

y=(-1)-2

y=-3

**Answer this Question**

**Related Questions**

Pre algebra - How do I solve Quadratic equations by factoring? (for example how ...

Pre Algebra - Can someone give me an example on how to solve a proportion. 6 e...

Pre-Algebra - How do you solve this Pre-Algebra problem: $1.25x + $2.25y = $916 ...

pre-algebra - it says use equivalent ratio's to solve the proportion!!! ok is ...

Biology of Environment - Complex systems have multiple sub systems, what would ...

algebra - How do I do substitution equations out of the equations in the system...

Math - Could someone give me an example of a linear eqution using elimination to...

Algebra II - We are learning how to solve systems using elimination. 2y - 1 = 3x...

Math (Algebra) - Could I have someone check my work please? If I did something ...

math/algebra - Solve the following systems: 2x + 2z =2 4x + 2y =3 2× + 2y + 2z =...